2021
DOI: 10.1111/myc.13261
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and Outcomes of Cryptococcemia patients with and without HIV infection

Abstract: Background The effects of cryptococcemia on patient outcomes in those with or without HIV remain unclear. Methods One hundred and seventy‐nine cryptococcemia patients were enrolled in this retrospective study. Demographic characteristics, blood test results and outcome were compared between the two groups. Results The diagnosis time of Cryptococcus infection was 2.0(0‐6.0) days for HIV‐infected patients, 5.0 (1.5‐8.0) days for HIV‐uninfected patients (p = .008), 2.0 (1.0‐6.0) days for cryptococcal meningitis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…As revealed by previous studies (Zhu et al, 2010;Fang et al, 2020;Fu et al, 2020;Zhou et al, 2020;Zhao et al, 2021), there are many more non-HIV patients in China than in other countries. In our study, we observed the same phenomenon: the proportion of patients with HIV was 12.78%.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…As revealed by previous studies (Zhu et al, 2010;Fang et al, 2020;Fu et al, 2020;Zhou et al, 2020;Zhao et al, 2021), there are many more non-HIV patients in China than in other countries. In our study, we observed the same phenomenon: the proportion of patients with HIV was 12.78%.…”
Section: Discussionmentioning
confidence: 80%
“…grubii ST5-VNI-α. Most patients (64.80–71.4%) with cryptococcosis were not infected with HIV, according to data from a general hospital in Zhejiang Province, which is also a designated HIV hospital ( Fang et al, 2020 ; Zhao et al, 2021 ). To collect more strains to further and more comprehensively explore the clinical characteristics, drug susceptibility and molecular characteristics of Cryptococcus spp.…”
Section: Introductionmentioning
confidence: 99%
“…One in three patients with CNS cryptococcosis in our cohort died within 12 months after diagnosis-a rate that is consistent with prior reports in immunocompromised populations. 1,3,4,20,21 Factors associated with mortality were fungaemia, extra-CNS involvement, requirement of ICU level of care and initial low CSF lymphocyte percentage-all measures that reflect the extent of involvement, clinical severity or degree of immunocompromise at presentation. One recent report found non-CNS extrapulmonary involvement to have a similarly high 90-day mortality rate as CNS cryptococcosis.…”
Section: Discussionmentioning
confidence: 99%
“…This group of opportunistic pathogens, primarily C. neoformans and C. gattii , affects the central nervous system (CNS) in up to 67% of patients 1,2 . Factors associated with poor outcomes with cryptococcosis include fungaemia, immunocompromised state, active malignancy, end‐stage liver disease, use of non‐amphotericin B‐based therapy and lack of intracranial pressure management 2–5 . Overall, the outcomes of cryptococcosis remain poor, with mortality rates as high as 80% depending on extent of infection and patient factors 1,4,6,7 …”
Section: Introductionmentioning
confidence: 99%
“…isolations, 42 patients with 79 Candida spp. isolations and 10 patients with 21 other fungal infections in CSF culture (Zhao et al, 2021). Ultimately, the 42 patients from whom Candida spp.…”
Section: Study Cohort and Patient Enrollmentmentioning
confidence: 99%